Paths out of poverty: Social entrepreneurship and sustainable development - Zhang, Xiaoyi; Sun, Yu; Gao, Yang; Dong, Yueqi (Frontiers in Psychology, 2022)
Poverty reduction in rural areas is an important development goal concerned by the international community, but the traditional poverty-reduction methods have certain drawbacks. From the perspective of social opportunity, this paper explores a new sustainable path for social entrepreneurship to solve the rural poverty. Using the case study method, this paper analyzes the social entrepreneurship process of 9 enterprises and the process mechanism of solving the rural poverty problem based on the identification and development of social opportunities. And we propose a conceptual framework for the sustainable development of social entrepreneurship. We find that social entrepreneurship is the process of identification, development and realization of social opportunities. Multidimensional rural poverty creates different social opportunities, including social opportunities in social, economic and ecological poverty. The company integrates farmers into its value chain to develop and realize social opportunities, which is a sustainable means of poverty alleviation. In terms of theory, this paper enriches the research on the process of realizing social opportunities in social entrepreneurship, and effectively answers the mechanism of promoting poverty alleviation in rural areas through social entrepreneurship. In terms of practice, it helps farmers master the ability to jointly develop social opportunities, and providing sustainable development ideas and resources for rural areas.